Development of Language Teaching Methodology Based on Innovative Technologies: The Role of Digital Resources in Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the application of innovative technologies and digital resources in language teaching methodology. The effectiveness of language learning through digital technologies in modern education, the introduction of new pedagogical approaches for teachers, and changes in the learning process for students are examined. The study explores the impact of interactive platforms, mobile applications, online resources, and distance learning systems on the educational process. Key principles and methodologies for the effective use of digital resources by teachers and students are outlined. The results confirm the role of digital technologies in enhancing success in language learning, while also discussing the challenges encountered in this process.